Inequality Across Space: A Sociological Imagination - Wida Ayu Puspitosari (Sociology Department, Brawijaya University, 2017)
In recent decades, the study of space has been truthfully appealing to social researchers, as it encourges them to walk through complexity of social life in which people engage to space. Space, all we know, is multiciplity dimension of the world in which we live.